Hospitalizations of HIV patients in a major Israeli HIV/AIDS center during the years 2000 to 2012. Issue 18 (May 2017) - Mahlab-Guri, Keren; Asher, Ilan; Bezalel-Rosenberg, Shira; Elbirt, Daniel; Sthoeger, Zev M.
Abstract : Abstract: To evaluate hospitalization rates and causes among human immunodeficiency virus (HIV) patients in the late highly active antiretroviral therapy (HAART) era. Data during the years 2000 to 2012 were obtained from hospital/clinical charts. Hospitalizations were defined as a ≥24 hours hospital admission. Obstetric admissions were excluded. Causes of hospitalizations were defined as acquired immune deficiency syndrome (AIDS)-defining illnesses, AIDS-related diseases (HAART adverse events, metabolic complications and non-AIDS-defining tumors/infections), and non-HIV-related diseases. Hospitalization rates are presented as admissions per 100 patient years. The number of HIV patients (58% males) in our center increased from 521 in 2000 to 1169 in 2012. 1676 hospital admissions (in 557 patients) were observed during the years of the study. The mean number of admissions per hospitalized patient was 3 ± 3.39. Hospitalization rates of HIV patients declined significantly (18.4/100 in 2000, 9/100 patient years in 2012; P  = .0001), but it was higher than the rates reported in the Israeli general population (X8.76 in 2000, X6.04 in 2012). Furthermore, hospitalizations for AIDS-defining illness declined (from 46.9% to 16.1%) whereas non-HIV-related hospitalizations increased (from 31.3% to 60.1%). Lower cluster of differentiation 4 (CD4) cell counts and older age, at the time of HIV diagnosis, were associated with higher rates of admissions (especially for AIDS-defining illnesses) and mortality. Hospitalization rates of HIV patients, especially for AIDS-defining illness, continue to decline in the late HAART era despite the increasing age of the patients, though it is still higher than that of the general population. Low CD4 cell counts and older age, at the time of HIV diagnosis, are associated with readmissions and mortality.